Warming‐Induced Effects on Microbial Communities and Nitrogen Cycling Capacity in Tundra Litter Are Modulated by Herb Abundance and Litter Quality - Mathilde Jeanbille; Karina E. Clemmensen; Jaanis Juhanson; Anders Michelsen; Juha Alatalo; Elisabeth J. Cooper; Greg H. R. Henry; Annika Hofgaard; Robert D. Hollister; Ingibjörg S. Jónsdóttir; Kari Klanderud; Anne Tolvanen; et al. (Global Change Biology, 2025)
Climate warming is changing tundra vegetation in the Arctic, with implications for plant litter properties. Warming may thus modify bacterial and fungal communities and their nitrogen (N) cycling capacity in the litter layer, which in turn can affect plant N availability. To address potential warming effects, we characterized the responses of bacterial and fungal communities and their genetically encoded capacity for inorganic N‐transformations in the litter layer, as well as 15 N natural abundance in the underlying soil layer as an integrated measure of N processes in the soil, in 16 long‐term alpine and Arctic tundra warming experiments distributed across 12 circumpolar locations. Although abundance, diversity, and composition of microbial communities were structured by the local conditions rather than experimental warming, warming indirectly modified microbial communities and their capacity for N transformations through changes in litter quality. Specifically, experimental warming resulted in stronger connections between the capacity for nitrification, denitrification and N‐fixation in the litter and the δ 15 N signature in the soil. These warming‐induced connections were mainly mediated by increased dominance of herbs but also increased litter mass. These findings suggest accelerated inorganic N cycling in the litter layer with warming, particularly coupled to local abundance of herbs, which can create positive feedback on plant growth as well as ecosystem respiration. Thus, microbial communities in the litter may contribute to an intensification of ongoing vegetation shifts across the tundra biome.

Dynamic response of soil microbial communities and network to hymexazol exposure - Cara Meyer; Mathilde Jeanbille; Marie-Christine Breuil; David Bru; Kristin Höfer; Claudio Screpanti; Laurent Philippot (Science of The Total Environment, 2024)

Size exclusion experiment in a grassland field unravels top–down control of the soil fauna on microbial community assembly - Mathilde Jeanbille; Sana Romdhane; Marie‐Christine Breuil; David Bru; Stefan Geisen; Arnaud Mounier; Aymé Spor; Laurent Philippot (Ecology Letters, 2024)
Highly diverse and abundant organisms coexist in soils. However, the contribution of biotic interactions between soil organisms to microbial community assembly remains to be explored. Here, we assess the extent to which soil fauna can shape microbial community assembly using an exclusion experiment in a grassland field to sort soil biota based on body size. After 1 year, the exclusion of larger fauna favoured phagotrophic protists, with increases up to 32% in their proportion compared to the no‐mesh treatment. In contrast, members of the bacterial community and to a lesser extent of the fungal community were negatively impacted. Shifts in bacterial but not in fungal communities were best explained by the response of the protistan community to exclusion. Our findings provide empirical evidence of top–down control on the soil microbial communities and underline the importance of integrating higher trophic levels for a better understanding of the soil microbiome assembly.

Soil microbial community fragmentation reveals indirect effects of fungicide exposure mediated by biotic interactions between microorganisms - Cara Meyer; Mathilde Jeanbille; Marie-Christine Breuil; David Bru; Kristin Höfer; Claudio Screpanti; Laurent Philippot (Journal of Hazardous Materials, 2024)

Metal contaminations impact archaeal community composition, abundance and function in remote alpine lakes - Sergi Compte‐Port; Carles M. Borrego; Hélène Moussard; Mathilde Jeanbille; Claudia Ximena Restrepo‐Ortiz; Alberto de Diego; Azibar Rodriguez‐Iruretagoiena; Ainara Gredilla; Silvia Fdez‐Ortiz de Vallejuelo; Pierre E. Galand; Dimitri Kalenitchenko; Jean‐Luc Rols; et al. (Environmental Microbiology, 2018)
Summary Using the 16S rRNA and mcrA genes, we investigated the composition, abundance and activity of sediment archaeal communities within 18 high‐mountain lakes under contrasted metal levels from different origins (bedrock erosion, past‐mining activities and atmospheric depositions). Bathyarchaeota, Euryarchaeota and Woesearchaeota were the major phyla found at the meta‐community scale, representing 48%, 18.3% and 15.2% of the archaeal community respectively. Metals were equally important as physicochemical variables in explaining the assemblage of archaeal communities and their abundance. Methanogenesis appeared as a process of central importance in the carbon cycle within sediments of alpine lakes as indicated by the absolute abundance of methanogen 16S rRNA and mcrA gene transcripts (10 5 to 10 9 copies g −1 ). We showed that methanogen abundance and activity were significantly reduced with increasing concentrations of Pb and Cd, two indicators of airborne metal contaminations. Considering the ecological importance of methanogenesis in sediment habitats, these metal contaminations may have system wide implications even in remote area such as alpine lakes. Overall, this work was pioneer in integrating the effect of long‐range atmospheric depositions on archaeal communities and indicated that metal contamination might significantly compromise the contribution of Archaea to the carbon cycling of the mountain lake sediments.